THE DEPICTION OF UTILITARIANISM IDEA ON THE MOVIE ENTITLED “UNTHINKABLE” - AKBAR, HOLY MUHAMMAD MUKMIN (Jurnal Ilmiah Mahasiswa FIB, 2014)
Key words: morality, utilitarianism, social realityThrough the development of knowledge, morality can no longer be a basic consideration to define the truth. This situation occurs because of the basic principle of modern knowledge which is based on empirism and rationalism has put morality as a value that is born by sentiments and not by logical reason. Because of this background, modern morality theories are designed to be accepted by scientific principle. One of them is called Utilitarianism. In order to put morality into society, one of the ways is by putting its values into literary works. Through the movie Unthinkable, the conflict between rationality and conscience is reflected. Based on those backgrounds, the focus of the study is formulized by the researcher in the moral dimension of literary work. The problem of the study is: How Utilitarianism is reflected on the movie entitled Unthinkable.The study is focused on the exploration of moral dimension of literary works through moral philosophical approach which place literary works as a product of society that reflects moral lesson. Mise-en-scene is also used to explore visual performance of the reflected moral theory Utilitarianism in the movie.In the end of the research, the result shows that there are several actions reflecting Utilitarianism principles. Those principles are reflected on the military activities in conducting the interrogation towards terrorist. Also on the other side, those principles appear in the terrorism activity. Those principles are depicted through two ways. From the verbal data, the debate appearing on the dialogue between characters reveals Utilitarianism principles used to justify whether an action is right or wrong. From the visual data, the Utilitarianism events are pictured dramatically as morally unaccepted actions. However, the movie also shows how important the application of Utilitarianism on that situation.The writer wants to give some suggestions for the next researcher about the different research  method that can be used. The next researcher can focus the research using dialectical method which is also applicable in analyzing literary product. Second, historical approach may develop the research to the next level by taking the second data source from US historical record about policies in war against terrorism.